Disks and outflows in the S255IR area of high mass star formation from ALMA observations. (August 2018) - Zinchenko, Igor; Liu, Sheng-Yuan; Su, Yu-Nung; Wang, Yuan
Abstract: We describe the general structure of the well known S255IR high mass star forming region, as revealed by our recent ALMA observations. The data indicate a physical relation exists between the major clumps SMA1 and SMA2. The driving source of the extended high velocity, well collimated bipolar outflow, is not the most pronounced disk-like SMA1 clump harboring a 20 M ⊙ young star (S255 NIRS3), as was assumed earlier. Apparently, it is the less evolved SMA2 clump, which drives the outflow and contains a compact rotating structure (probably a disk). At the same time, the SMA1 clump drives another outflow, with a larger opening angle. The molecular line data do not show an outflow from the SMA3 clump (NIRS1), which was suggested by IR studies of this region.